Thermodynamics And Its Quantum Correction Of Vacuum Nonsingular Black Hole - D. Ma; T. Huo; C. Liu
This paper investigates the thermodynamic properties of vacuum nonsingular black holes. Considering the energy characteristics of the regularity spacetime, we use the modified first law of black hole thermodynamics to calculate the black holes' Hawking temperature, entropy and heat capacity. The obtained temperature is the same as that obtained by the surface gravity and tunneling methods. Also, the entropy is satisfied with the Bekenstein-Hawking area law. Notably, the heat capacity of large-mass black holes diverges, while that of small-mass black holes tends to zero, with a phase transition point existing. Additionally, we consider the quantum gravity effect by using the generalized uncertainty principle to study the quantum corrections of the thermodynamic properties for the vacuum nonsingular black holes. The generalized uncertainty principle introduces a logarithmic correction term to the black hole entropy. Also, the temperature and heat capacity are modified. В данной статье исследуются термодинамические свойства вакуумных несингулярных черных дыр. Учитывая энергетические характеристики регулярного пространства-времени, использован модифицированный первый закон термодинамики черных дыр для расчета температуры Хокинга, энтропии и теплоемкости черных дыр. Полученная температура совпадает с температурой, полученной методами поверхностной гравитации и туннелирования. Кроме того, энтропия удовлетворяет закону площади Бекенштейна- Хокинга. Примечательно, что теплоемкость черных дыр большой массы расходится, в то время как теплоемкость черных дыр малой массы стремится к нулю, при этом существует точка фазового перехода. Кроме того, эффект квантовой гравитации рассматрен использованием обобщенного принципа неопределенности для изучения квантовых поправок термодинамических свойств в случае вакуумных несингулярных черных дыр. Обобщенный принцип неопределенности вводит логарифмический поправочный член в энтропию черной дыры. Также модифицируются температура и теплоемкость.
Keywords: Thermodynamics